Investigation of the Possible Toxicological Effects of Paracetamol on Lung in the Trimesters; An Experimental Study - İlyas Ucar; Seher Yılmaz; Muhammet Değermenci; Adem Tokpınar; Şükrü Ateş; Ayşe Yeşim Göçmen; Mehtap Nisari; Erdoğan Unur (Indonesian Journal of Pharmacy, 2022)
Paracetamol (PAR) is an analgesic and antipyretic drug that is frequently used during pregnancy in many countries of the world. Although the fetal and maternal effects of toxic or long-term therapeutic doses used during pregnancy are known, the data on fetal effects during trimesters are insufficient. In this study, the possible effects of PAR exposure on both maternal and fetal tissues were investigated during pregnancy and in different trimester periods. Pregnant rats were exposed to different doses of PAR (low dose: 50 mg/kg and high dose: 500 mg/kg) in first trimester (1-7th days), second trimester (8-14th days) and third trimester (15-21st days) of pregnancy. On the 21st day, fetuses were removed by cesarean section under anesthesia. Maternal and fetal lung tissues samples were taken for biochemical analysis. PAR exposure decreased antioxidants levels and increased oxidative stress parameters levels in maternal and infant lung tissues. TBARS and TOS values increased compared to the control group, and it was statistically significant in all groups except the 1LD group (p <0.05). SOD, CAT, GPX, TAS, and GSH parameters decreased compared to the control group, which was statistically significant in maternal lungs (p <0.05). In infant lungs, it was also statistically significant for all groups in SOD, CAT, and TAS parameters. This experimental study demonstrates that exposure to PAR during pregnancy caused toxic damage to both maternal and fetal lung organs, especially in long-term usage during pregnancy, and in the third trimester.